KONTRAST NUTQ VA FIKRLASHNING KOGNITIV UNIVERSALLIGI SIFATIDA («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article analyzes whether the concept of contrast is a cognitive state associated with the human mind and being. Although the terms contrast and opposition are similar in meaning, their object is explored in different aspects.
Keywords: contrast, antithesis, privative feature, graded content, equivalence, opposition.